ACTUAL AND INTELLECTUAL ARROWSHOTS IN SOPHRON (FRR. 50 AND 86 KASSEL–AUSTIN). (December 2022) - Cassio, A. C.
Abstract : After some notes on the remarkable linguistic difficulties encountered by ancient Athenian readers of Sophron's text, this article will deal with the textual and interpretative problems posed by two fragments of the mimes that are more significant than it may appear at first sight. It is argued that a verbal form transmitted in fr. 86 K–A, whose correctness has systematically been doubted, is in fact linguistically unassailable and used in the description of an ambush that might be either military or metaphorical. As to fr. 50, once the correct reading of the principal verb has been established, we recover a subtle metaphor used by a character in a mime to criticise those who make hasty speculations about things unknown –something that reveals a sophistication rarely encountered in other fragments, and provides us with a glimpse into the reasons why Sophron's mimes enjoyed such respect in antiquity.